Perancangan Sistem Informasi Hubungan Mitra Kerja Untuk Pendidikan Menengah Kejuruan Berbasis Web (Studi Kasus SMK Negeri 2 Padang) - Putra, Fikri Pratama (Jurnal Teknik Komputer dan Informatika, 2024)
The Work Partnership Information System is a web-based application designed to enhance collaboration between SMK Negeri 2 Padang and industrial partners in support of vocational secondary education. This research aims to design and implement an information system that enables effective communication, information sharing, and partnership development between the school and industry partners. This study is designed using the Waterfall method. Data is collected through interviews with school and industry partners and observations of the existing collaboration processes. The research results indicate that the implemented information system facilitates more efficient information exchange and communication between the school and industry partners. This, in turn, helps improve the quality of vocational education, student internship placements, and the monitoring of students' progress in the industrial world. Therefore, this information system makes a positive contribution to vocational secondary education at SMK Negeri 2 Padang, enhances work partnership relationships, and benefits students, teachers, and industrial partners. The findings of this research can serve as a reference for similar educational institutions seeking to enhance collaboration with industry partners through the utilization of web-based information technology.